Modification of a previously patented method to unequivocally score A2-like and A1-like bovine β-casein variants - Raschia, Maria Agustina (2023)
A growing interest in the production and commercialization of A2 cow's milk has been observed in many countries in the last few years due to the beneficial properties for human health attributed to A2 β-casein variant. Methods of varying complexity and different equipment requirements have been proposed for the determination of the β-casein genotype of individual cows. We proposed herein a modification of a previously patented method based on an amplification-created restriction site PCR followed by restriction fragment length polymorphism analysis. This method allows to identify and differentiate A2-like from A1-like β-casein variants, after differential endonuclease cleavage flanking the nucleotide that determines the amino acid at position 67 of β-casein. The advantages of this method are that it: • enables to unequivocally score A2-like as well as A1-like β-casein variants, • can be performed at low cost in simply equipped molecular biology laboratories, and • can be scaled up to analyze hundreds of samples per day. For these reasons, and based on the results obtained from the analysis carried out in this work, it showed to be a reliable method for the screening of herds to selective breeding of homozygous cows and bulls for A2 or A2-like alleles.